Recorded Music: Philosophical and Critical Reflections - Doğantan-Dack, Mine (London Middlesex University, 2008)
In recent musicology, performances rather than musical scores have come to be regarded as the foundation of music. Recordings preserve performances, thus allowing researchers to scrutinise them in detail through repeated hearings, and are rapidly becoming the object of academic study. Recorded Music: Philosophical and Critical Reflections brings together a collection of international experts to explore philosophical and critical issues surrounding music recordings. Edited by the Chair of the Music Research Group at Middlesex University, Dr Mine Doðantan-Dack, the book addresses questions relating to temporality, recorded time, spatiality, musical reality, intertextuality and more. Whilst a number of books to date have documented the changing performance styles and the impact of technology on performance traditions through study of recordings, Recorded Music: Philosophical and Critical Reflections is the first to address philosophical and critical questions pertaining to recordings in the form of an anthology. The book brings together the perspectives of practising musicians, musicologists, sound artists, and recording engineers on the philosophical and critical issues related to their work in the context of making and using recordings. Fully illustrated with musical examples, this book will appeal to musicologists, ethnomusicologists and practising musicians involved in Western art music, jazz, popular music and world music, as well as being of interest to sound artists and recording engineers. The companion CD includes excerpts from the original works discussed by the contributing practitioners of music, and an original studio performance by the editor.
Keywords: Music philosophy and esthetics; Performance; Technology